Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Sebagai Penerapan Kurikulum 2013 Pada Mata Pelajaran Praktikum Akuntansi Perusahaan Jasa Kelas XI Akuntansi Di SMK Negeri 1 Surabaya - Anisah Nurwandini; Joni Susilowibowo (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2020)
This development research aims to analyze the process of development, feasibility, and response of product learners Student Activity Sheet Services Company Accounting Practicum in the Documentation and Recording phase. The development model used in this study is 4-D by Thiagarajan with the stages of define, design, develop, and disseminate. The research instruments used were study sheets and validation, as well as students' responses to the validation results of the material experts for the content component by 80% and the presentation component by 82.222%, linguists by 80%, graphic experts by 90.909% with the results of the feasibility component by 83.283 % of the categories are said to be